AGRESIVITAS DAN VIOLENSIA - Simorangkir, Hieronymus (LOGOS, 2002)
There is a number of distinctions regarding the nature of aggression and itsfunction. Therefore it is necessary to elucidate clear differences between theactive engagement in gaining mastery over the environment for survival’ssake, and self defence with force when threatened, and enjoyment oftorturing, controlling, or killing without provocation or real need. Of theseexplanations it would elucidatively appear that aggression and violencediffer, but both interact one another.